Dissociative Adsorption of Hydrogen in Hydrogen-Blended Natural Gas Pipelines: A First Principles and Thermodynamic Analysis - Wei He; Zhenmin Luo; Pengyu Zhang; Ruikang Li; Xi Yang (Applied Sciences)
This study employs first principles calculations and thermodynamic analyses to investigate the dissociative adsorption of hydrogen on the Fe(110) surface. The results show that the adsorption energies of hydrogen at different sites on the iron surface are −1.98 eV (top site), −2.63 eV (bridge site), and −2.98 eV (hollow site), with the hollow site being the most stable adsorption position. Thermodynamic analysis further reveals that under operational conditions of 25 °C and 12 MPa, the Gibbs free energy change (ΔG) for hydrogen dissociation is −1.53 eV, indicating that the process is spontaneous under pipeline conditions. Moreover, as temperature and pressure increase, the spontaneity of the adsorption process improves, thus enhancing hydrogen transport efficiency in pipelines. These findings provide a theoretical basis for optimizing hydrogen transport technology in natural gas pipelines and offer scientific support for mitigating hydrogen embrittlement, improving pipeline material performance, and developing future hydrogen transportation strategies and safety measures.